Reproductive Health - Belizán, José M.; Mumford, Sunni
Reproductive Health publishes content on all aspects of human reproduction. The journal includes sections dedicated to adolescent health, female fertility and midwifery and all articles are open access. Reproductive Health has a particular interest on the impact changes in reproductive health have globally, and therefore encourages submissions from researchers based in low- and middle-income countries.